EFEKTIVITAS MEDIA ULAR TANGGA DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PENJUMLAHAN DAN PENGURANGAN SISWA KELAS II SD N KLOPOGODO KABUPATEN KEBUMEN - Khasanah, Isna Yatul; Sukasih, Sri (De Fermat : Jurnal Pendidikan Matematika, 2026)
The low level of addition and subtraction skills among elementary school students remains a common problem, particularly due to conventional teaching methods that make limited use of engaging learning media. The use of game-based learning media, such as the Snakes and Ladders game, is considered capable of creating a more interactive and enjoyable learning environment, thereby increasing student engagement. This study aims to determine the effect of using Snakes and Ladders as a learning medium on the numeracy skills of second-grade students at SD Negeri Klopogodo, Kebumen. The research employed a quantitative approach with a pre-experimental method, involving all students in one class as the research subjects. Data were collected through pre-test and post-test assessments, supported by observation, interviews, and documentation techniques. The results indicate an improvement in students’ numeracy skills after the implementation of the Snakes and Ladders learning media in the teaching process. This medium helps students understand the concepts of addition and subtraction more easily through enjoyable learning activities. Therefore, Snakes and Ladders can be considered an effective alternative learning medium to improve elementary school students’ numeracy skills.